PHYSICAL ACTIVITY, COGNITIVE HEALTH, AND LONGEVITY IN OLDER ADULTHOOD. (20th December 2022) - Yoneda, Tomiko; Piccinin, Andrea; Lewis, Nathan; Knight, Jamie; Hyun, Jinshil; Kleineidam, Luca; Hofer, Scott; Terrera, Graciela Muniz
Abstract: Research suggests that physical activity (PA) protects against cognitive impairment in older adulthood; however, the extent to which PA engagement throughout older adulthood influences the simultaneous risk of transitioning to cognitively impaired states and death is unclear. Applying coordinated data analysis across 14 studies, multi-state survival models (MSM) were independently fit to data from fourteen longitudinal studies (NTotal=52, 039). PA was synthesized across studies using the metabolic equivalent of task approach. Adjusting for demographics and chronic conditions, meta-analytic results indicated that engaging in more PA was associated with a reduced risk of transitioning from no cognitive impairment to mildly impaired cognitive functioning (HR=0.94, 95%CI's=0.89, 0.99) and death (HR=0.72, 95%CI's=0.65, 0.80). Based on MSM estimates, multinomial regression models computed total life expectancy stratified by national PA recommendations. Meta-analytic results indicate a positive linear effect of PA, such that more PA is associated with longevity. This presentation will include discussion of knowledge translation efforts.